Rhizodeposition and litter decomposition of Phragmites australis play important roles in composition and properties of soil dissolved organic matter. (September 2022) - Cui, Yuan; Luo, Fang-Li; Chen, Yu-Han; Zhang, Ming-Xiang; Yu, Fei-Hai
Graphical abstract: Highlights: Effects of plant C inputs on composition and properties of soil DOM were estimated. Plant C was from either rhizodeposits or decomposition of different tissue litters. Rhizodeposition and litter decomposition had significant effects on soil DOM. Effects of rhizodeposition on soil DOM were significantly altered by salinity. Effects of litter on soil DOM varied greatly among plant tissue types. Abstract: The dynamics of composition and properties of dissolved organic matter in soil depend on plant carbon inputs and microbial degradation. However, uncertainties remain regarding the relative contributions of different plant carbon inputs sources, i.e., from litter decomposition versus rhizodeposits, to soil dissolved organic matter, which may limit the understanding of soil carbon dynamics. In this study, effects of plant carbon inputs from either rhizodeposition or litter (leaf, stem, rhizome, and root litter) decomposition on composition and optical properties of soil dissolved organic matter were estimated. Rhizodeposition and litter decomposition of P. australis had significant effects on soil dissolved organic matter, and its variation was mainly associated with the third fluorescent component (C3). Effects of rhizodeposition on soil dissolved organic matter were significantly altered by soil salinity, exhibiting increased chromophoric dissolved organic matter and fulvic acid C3 under saline conditions. Effects of litter decomposition on soil chemistry and dissolved organic matter varied greatly among plant tissues. Compared with rhizome and root, leaf and stem decomposed more thoroughly and significantly increased the contents of fulvic acid C3. This was supported by increased aromaticity associated with leaf inputs and increased plant-derived dissolved organic matter associated with stem and leaf inputs. These findings highlight the significant influence of rhizodeposition and litter decomposition on soil dissolved organic matter, and suggest that the roles of salinization and plant tissue type merit consideration in further studies on plant–soil carbon cycling.